PERILAKU SUFI SEMASA REMAJA (Studi atas Tasawuf Akhlaki dalam Persefektif Muhammad Idris Jauhari) - Moh. Samhadi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2018)
Sufi behavior is a noble act, because in daily implementation is the application of hakeki Islamic teachings. The purpose of such implementation is to reach the level of Ihsān. But at this time there is a wrong assumption about the stuffiness of Sufism, so there is an assumption that people who can carry out Sufism are only certain people. So this, can be an obstacle for people who want to apply it in everyday life, especially teenagers. To find out more about it, researchers use a qualitative research approach that is the study of figures. The methods used are verstehen methods, interpretation, history, description, and induction. From this method, researchers then analyzed the existing data, so that some concepts of Muhammad Idris Jauhari's thinking, including to apply Sufi behavior during adolescence is not an obstacle for a teenager, because basically humans are created to worship Him. With regard to the application of Sufi behavior during adolescence is very appropriate to do for a teenager. Which at this time is a time of very productive development, if not built properly morally it will have an impact on the next phase. Therefore, it is very fitting that the application of Tasawuf akhlaki that prioritizes moral aspects.